Internalizing Anti-Sexual Violence Education as a Preventive Strategy Against Risky Sexual Behavior Among Adolescents - Nadifah Nadifah; Umar Manshur; Najiburrohman Najiburrohman; Tohet Tohet; Ahmad Wahdi (Seutia Hukamaa Cendekia, 2025)
This study aims to examine the internalization of anti-sexual violence education as a preventive strategy against risky sexual behavior among adolescents. The research employs a qualitative approach with a case study design to explore deeply the implementation process, strategies, and impacts within educational settings. Data were collected through observations, semi-structured interviews, and documentation, and analyzed using data condensation, data display, and verification techniques. The findings reveal that the internalization process, carried out through habituation, role modeling, and reinforcement, significantly enhances students’ awareness of personal boundaries, improves social interactions, and strengthens their ability to avoid risky behavior. In addition, supportive school environments and teacher involvement play crucial roles in the effectiveness of this process, although cultural barriers remain challenges. The study implies that integrating cognitive, affective, and behavioral dimensions in education is essential to achieve meaningful and sustainable behavioral change among adolescents, particularly in preventing sexual violence and promoting ethical conduct.